Oral Contraceptives and Platelet Function - Mettler, L; Selchow, Meseck B. (Thrombosis and Haemostasis, 1972)
Platelet function was studied in women receiving two oral oestrogen-progestagen compounds (Neogynon and Noracyclin-22). Platelet count, adhesiveness, spreading, aggregation (PAT) and thromboelastography (TEG) were studied twice monthly for six months in 186 cycles. Platelet counts in rotated plasma were decreased in both groups. A significant increase in non-spread platelets was found in the Neogynon group only. PAT-degrees were significantly increased in both groups. Platelet adhesiveness and thromboelastographic measurements were not affected. Increased platelet aggregation during oral contraceptive therapy is regarded as a predisposing factor to thrombosis.